2020
DOI: 10.3390/ijms21072351
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind Retinal Ganglion Cell Loss in Diabetes and Therapeutic Approach

Abstract: Diabetes produces several changes in the body triggered by high glycemia. Some of these changes include altered metabolism, structural changes in blood vessels and chronic inflammation. The eye and particularly the retinal ganglion cells (RGCs) are not spared, and the changes eventually lead to cell loss and visual function impairment. Understanding the mechanisms resulting in RGC damage and loss from diabetic retinopathy is essential to find an effective treatment. This review focuses mainly on the signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 172 publications
(191 reference statements)
1
20
0
Order By: Relevance
“… 46 Diabetes also induces changes in blood vessels and chronic inflammation in the retina and eventually caused retinal ganglion cell loss. 47 Our data showed apparently increased inflammatory cells infiltration and significant elevated inflammatory cytokines expression in the MG of DM rats. ERK1/2 NF-κB plays an important role in regulating inflammatory responses.…”
Section: Discussionsupporting
confidence: 53%
“… 46 Diabetes also induces changes in blood vessels and chronic inflammation in the retina and eventually caused retinal ganglion cell loss. 47 Our data showed apparently increased inflammatory cells infiltration and significant elevated inflammatory cytokines expression in the MG of DM rats. ERK1/2 NF-κB plays an important role in regulating inflammatory responses.…”
Section: Discussionsupporting
confidence: 53%
“…Post-translational modifications in general, and phosphorylation in particular, are key mechanisms of regulation of protein function, a phenomenon well-characterized for αB-crystallins. Phosphorylation of HspB5/αB-crystallin can be induced by MAPKs including extracellular-signal-regulated kinase (ERK) and p38 under stress conditions [ 48 , 49 ], which eventually regulates its intracellular distribution, translocation, and chaperone activity [ 50 , 51 ] and also enhances its anti-apoptotic potential [ 52 ]. Although, earlier in vivo studies had shown HspB4/αA-crystallin in the lens can be phosphorylated at residue-122 and 148, unlike HspB5/αB-crystallin, detailed functional studies for HspB4/αA-crystallin phosphorylation are very limited [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modi cations in general, and phosphorylation in particular, are key mechanisms of regulation of protein function, a phenomenon well-characterized for aB-crystallins. Phosphorylation of αB-crystallin can be induced by MAPKs including extracellular signal-regulated kinase (ERK) and p38 under stress conditions (46,47), which eventually regulates its intracellular distribution, translocation, chaperone activity (48,49) and also enhances its anti-apoptotic potential (50). Although, earlier in-vivo studies had shown αA-crystallin in the lens can be phosphorylated at residue-122 and 148, unlike αBcrystallin, detailed functional studies for αA-crystallin phosphorylation are very limited (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%